Effectiveness of Nivolumab in second-line and later in patients with advanced non-small cell lung cancer in real-life practice in France and Germany: analysis of the ESME-AMLC and CRISP cohorts - Chouaid, Christos; Thomas, Michael; Debieuvre, Didier; Durand-Zaleski, Isabelle; Zacharias, Stefan; Bosquet, Lise; Groth, Annika; Fleitz, Annette; Calleja, Alan; Patel, Sonya; Lacoin, Laure; Daumont, Melinda J.; et al. (Cancers, 2022)
This study reports characteristics and outcomes in patients with locally advanced or metastatic non-small cell lung cancer (aNSCLC) receiving nivolumab in second-line or later (2L+) in France and Germany between 2015 and 2020. Patients with aNSCLC (stage IIIB-C/IV) receiving nivolumab in 2L+ were included from the retrospective Epidemiological Strategy and Medical Economics of Advanced and Metastatic Lung Cancer cohort (ESME-AMLC, France; 2015-2019) and Clinical Research platform Into molecular testing, treatment and outcome of non-Small cell lung carcinoma Patients (CRISP, Germany; 2016-2020). Overall, 2262 ESME-AMLC and 522 CRISP patients were included. Median treatment duration (95% confidence intervals) was 2.8 months (2.5-3.2) in squamous and 2.5 months (2.3-2.8) in non-squamous/others patients in ESME-AMLC, and 2.3 months (1.4-3.1) and 2.3 months (2.0-2.8), respectively in CRISP. One-year and two-year overall survival (OS) were 47.2% and 26.7% in squamous and 50.8% and 32.8% in non-squamous/others patients in ESME-AMLC, and 43.1% and 20.9%, and 37.7% and 18.9%, respectively in CRISP. Poorer performance score and shorter time from start of previous line of therapy initiation were significantly associated with shorter treatment duration and OS. This study confirms, in real-world clinical databases, the efficacy of nivolumab previously observed in clinical trials.
Gesehen am 31.01.2023